Programme management principles as critical success factors for the realisation of post-implementation benefits from an ERP implementation - Bindeman, Konrad (My University, 2016)
The purpose of this research was to determine whether principles promoted by a programme management discipline be defined as critical success factors (CSFs) for the realisation of post-implementation benefits from an ERP investment in an organisation. The research method consists of a single case study with three embedded cases. The main source of data was the use of semi-structured interviews, and business documentation was used to corroborate findings. It was concluded that of the eleven CSFs proposed, three were highly likely CSFs, seven were likely but had certain conditions attached, and one is most likely not a CSF. It was also discovered that four additional CSFs proposed in interviews conducted may be relevant, and that four themes exist within the case data analysed. These may form part of future work.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Science, Industrial Engineering, 31 March 2015
Keywords: Project management; Enterprise resource planning; Business planning; Management information systems